SISTEM PENUNJANG KEPUTUSAN PEMILIHAN SEKOLAH LUAR BIASA DENGAN METODE FUZZY MULTIPLE CRITERIA DECISION MAKING - Ferdy Ferdy; Dedy Trisnawarman; Zyad Rusdi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
Decision support system has many methods that can be used by decision makers. one of the methods is fuzzy multiple criteria decision making (FMCDM) this method will help decision makers to make the final decision with regard to multiple criteria decision alternatives. This final task will be to apply the decision support system with fuzzy multiple criteria decision making to determine the selection of special schools.